Mechanisms of cell cycle arrest in response to TGF-beta in progestin-dependent and -independent growth of mammary tumors - Salatino, Mariana (2001)
TGF-beta1 modulation of cell cycle components was assessed in an experimental model in which the synthetic progestin medroxyprogesterone acetate (MPA) induced mammary tumors in Balb/c mice. TGF-beta1 inhibited both MPA-induced proliferation of progestin-dependent C4HD epithelial cells and proliferation of the progestin-independent variant cell type C4HI, arresting cells in G(1) phase of the cell cycle. Progestin-independent 60 epithelial cells evidenced reduced response to TGF-beta1 antiproliferative effects. TGF-beta1 inhibition of cyclins D1 and A expression and up-regulation of p21(CIP1) levels were the common findings in all three cell types. In addition, a significant content reduction of cyclin D1/cdk4 and cyclin A/cdk2 complexes was found after TGF-beta1 inhibition of MPA-dependent and -independent proliferation. TGF-beta1 inhibited cyclin D2 expression and up-regulated p27(KIP1) levels only when acting as inhibitor of MPA-induced proliferation of C4HD cells. Regulation of these two cell cycle components resulted in decreased cyclin D2/cdk2 complex and in increased p27(KIP1) association with cdk2 in C4HD cells treated with TGF-beta1. These two molecular mechanisms, unobserved in progestin-independent growth of C4HI or 60 cells, were associated with a significantly higher degree of inhibition of cdk2 kinase activity in C4HD cells compared to that found in TGF-beta-treated C4HI or 60 cells. Reduced sensitivity of 60 cells to the growth-inhibitory effects of TGF-beta1 correlated with significantly lower levels of p15(INK4B), p21(CIP1), and p27(KIP1) expressed in these cells, compared to the levels present in C4HD or C4HI cells, and correlated as well with lack of expression of p16(INK4). Thus, common targets were found to exist in TGF-beta1 inhibitory action on breast cancer cells, but regulation of specific targets was found when TGF-beta1-inhibited proliferation driven by the progesterone receptor.